Language training at school and university: systematization and generalization of the experience of using trilingualism - Abisheva, M.B.; Ibadullayeva, S.Zh.; Tavstukha, O.G.; Sagimbayeva, G.S.; Begenova, A.B. (KU Publ., 2022)
Modern society makes serious demands on language education in schools and universities, and issues of improving its quality are important both for a particular native language and for the state as a whole. This is due to a number of reasons. Today, language training in schools and universities is a prerequisite and requirement of the time. The article discusses methods of increasing linguistic competence when using the native language and more than two foreign languages, in the future this may be aimed at mastering one or more foreign languages. At the same time, the idea of expanding the pedagogical capabilities of this technology is emphasized, firstly, by combining various types of exercises that make up the complex in the form of training, and secondly, by highlighting new types of exercises (linguistic, conditional). Teaching a modern subject language must comply with the principles of effective communication in a trilingual program system.
Мектептегі және университеттегі тілдік дайындық: үштілділікті қолдану тәжірибесін жүйелеу және қорыту
Языковая подготовка в школе и вузе: систематизация и обобщение опыта использования трехъязычия
Keywords: trilingualism; education; development; competence; students; multilingualism; language training; language competence